A Smart Design Strategy for Super‐Elastic Hydrogel with Long‐Term Moisture, Extreme Temperature Resistance, and Non‐Flammability. Issue 16 (19th June 2021) - Zhang, Haiquan; Liu, Zijing; Mai, Junping; Wang, Ning; Liu, Houji; Zhong, Jie; Mai, Xianmin
Abstract: Elastic hydrogel is a promising material category for designing biological muscles, repairable building materials, flexible electronic devices, and vulcanized rubber substitutes, which is required to have a long life, good self‐healing performance and extreme temperature tolerance. Herein, a super‐elastic mineral hydrogel is developed with long‐lasting moisture, based on dynamic physical crosslinking between hydrated calcium ion clusters and amide groups of polyacrylamide (PAM). The complex hydrogel exhibits a super stretchability of 13 600% at room temperature, and can maintain the super flexibility in a wide temperature range of −40–50 °C or for a long period of 28 days. Particularly, the soft material cannot be ignited under an open flame at 400–500 °C, because of coupling dual flame retardant mechanisms containing the endothermic effect of liquid water evaporation and the barrier effect of calcium mineral salt on oxygen. In conclusion, the novel complex hydrogel with excellent tensile property, stability in extreme temperature or long operating time, and flame retardancy may become a promising candidate in the fields of agriculture, food, construction, medicine, and machinery. Abstract : Dynamic physical crosslinking of calcium (II) with in situ polymerized polyacrylamide provides a new mechanism for stress/energy dispersion of soft materials during stretching. As‐prepared complex hydrogel exhibits stable mechanical performance for a long‐term or under extreme temperature, and has ideal flame‐retardant ability due to the water‐locking effect of calcium (II) and barrier effect on oxygen.